Teacher Satisfaction, Self-Efficacy Affect on Teacher Performance: An Evidence from A Vocational School of Pharmaceutical Study Program East Borneo, Indonesia - M. Rajib Bustami; Azainil Azainil; Laili Komariah (PT ARRUS Intelektual Indonesia, 2022)
This study aims to analyze the effect of teacher satisfaction, self-efficacy, and burnout on teacher performance in vocational schools in East Kalimantan. The method used in this research is quantitative. This study uses a questionnaire that has been validated and tested its reliability on 118 teachers. The data collection technique used a questionnaire to obtain data on teacher satisfaction, self-efficacy, and teacher performance. Data analysis with instrument validation of the three variables using Pearson correlation and reliability using Cronbach alpha, while for the approach using multiple linear regression analysis. The results showed that (1) teachers had a significant effect on teacher performance, meaning that higher teacher satisfaction resulted in an increase in teacher performance, (2) self-efficacy had a significant effect on teacher performance, (3) teacher goals and teacher self-efficacy jointly affected performance. teacher. significant on teacher performance. Results Based on the research, it can be concluded that the performance of teachers in the Pharmacy Study Program Vocational School can be improved through satisfaction and self-efficacy.